2020
DOI: 10.3390/s20216006
|View full text |Cite
|
Sign up to set email alerts
|

Generating Time-Series LAI Estimates of Maize Using Combined Methods Based on Multispectral UAV Observations and WOFOST Model

Abstract: Green leaf area index (LAI) is an important variable related to crop growth. Accurate and timely information on LAI is essential for developing suitable field management strategies to mitigate risk and boost yield. Several remote sensing (RS) based methods have been recently developed to estimate LAI at the regional scale. However, the performance of these methods tends to be affected by the quality of RS data, especially when time-series LAI are required. For crop LAI estimation, supplementary growth informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Tiller number counting could contribute to estimating current crop partitioning parameters by combining other observables such as biomass. The growth-model prediction could enhance accuracy through data assimilation with phenotyping results [ 32 , 33 ]. Data-assimilation methods with panicles and tillers could be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Tiller number counting could contribute to estimating current crop partitioning parameters by combining other observables such as biomass. The growth-model prediction could enhance accuracy through data assimilation with phenotyping results [ 32 , 33 ]. Data-assimilation methods with panicles and tillers could be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Although the accuracy of the results from these studies was acceptable, an increase in variety of input of variables could improve the accuracy of the models further (Khaliq et al, 2018;Fu et al, 2020;Zhou et al, 2020). Cheng et al (Cheng et al, 2020) determined the LAI of maize based on VI, crop models, and data assimilation methods, achieving improved accuracy compared to any single method. Shu et al (Meiyan et al, 2022) constructed a prediction model for the aboveground biomass of maize in multiple growth periods by combining multispectral and UAV digital images with maize LAI and plant height.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of researchers have conducted studies in the eld of remote sensing for agricultural products (Zhu et al, 2019;Zhang et al, 2021), chlorophyll content (Zhang et al, 2021;Xie et al, 2019), water and nitrogen content (Thorp et al, 2018;Marang et al, 2021). Many studies have also focused on remote sensing tools, such as hand-held spectrometers (Dong et al, 2019), drones (Cheng et al, 2020), and satellites (Fang et al, 2015;Dong et al, 2020). Studies have shown that satellite images have good potential in estimating the leaf area index (Gaso et al, 2021).…”
Section: Introductionmentioning
confidence: 99%